Tadrīs Mahārah al-Istimā’ Ligahiri an-Nāţiqīna Bi al-‘Arabiyyah Min Khilāli Kitābi Silisilati Ta’līmi al-Lughah al-‘Arabiyyah - Fajar Rachmadhani (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
Tadrīs Mahārah al-Istimā’ Ligahiri an-Nāţiqīna Bi al-‘Arabiyyah Min Khilāli Kitābi Silisilati Ta’līmi al-Lughah al-‘ArabiyyahFajar RachmadhaniUniversitas Muhammadiyah Yogyakartafajarrachmadhani@umy.ac.idAbstractThe listening skill is the first and most important skill the child experiences in acquiring the mother tongue. The child starts his external relationship with him through listening. It is known that the skill of listening is necessary in human life, because it is the means of communication between people in the way of earning vocabulary, and learn the types of sentences and structures, knowledge of ideas and concepts, etc., the prerequisite for this skill is the ability of the listener to distinguish audible voices. It is true that a student may read and write in a foreign language without improving the communicative aspect of hearing comprehension and speech, but he remains unable to use the language correctly. In addition, the method of teaching listening skills to students, especially non-Arabic speakers, is more important than the listening skill itself, so that the method is more important than the material. Therefore, the teachers of Arabic language for non-native speakers must pay attention to the attention during their teaching of great interest. This research discusses the role of listening skill and teaching method for non-Arabic speakers through the book of the series of Arabic language instruction issued by Imam Muhammad bin Saud Islamic University in Saudi Arabia, so that this book is taught in various universities and institutes of Arabic language teaching in Indonesia.Keywords: Mahārah al-Istimā’, Tadrīs al-Lughah, Kitāb Silsilahتدريس مهارة الاستماع لغير الناطقين بالعربية من خلال كتاب "سلسلة تعليم اللغة العربية "فجر رحمادانيجامعة محمدية يوكياكرتاfajarrachmadhani@umy.ac.idالملخصتعتبر مهارة الاستماع أولى المهارات وأهمها التي يمر بها الطفل في اكتساب لغة الأم، كما أن الاستماع هو الفن الأول الذي يتعامل معه الطفل، فالطفل يبدأ علاقاته الخارجية بمن حوله عن طريق الاستماع ، فتبدأ مهارات الاستماع بالنمو قبل غيرها. ومن المعلوم أن مهارة الاستماع شيء لازم في حياة الانسان، لأنها وسيلة الاتصال بين الناس بطريقة كسب المفردات، ويتعلم أنواع الجمل والتراكيب، معرفة الأفكار والمفاهيم وغير ذلك، فالشرط الأساسي لهذه المهارة هو قدرة السامع بتمييز الأصوات المسموعة. صحيح، أن الطالب قد يقرأ ويكتب في اللغة الأجنبية من غير أن يحسن الجانب الإتصالي من فهم مسموع وكلام، ولكنه يبقى غير قادر على استخدام اللغة استخداما صحيحا. إضافة إلى ذلك، أن طريقة تدريس مهارة الاستماع للطالب وخاصة لغير الناطقين بالعربية أهم من مهارة الاستماع نفسها، بحيث أن الطريقة أهم من المادة. لذا يجب على مدرسي اللغة العربية لغير الناطقين بها أن يهتم الجانب الاستماعي خلال تدريسهم اهتماما بالغا. يتحدث هذا البحث عن دور مهارة الاستماع وطريقة تدريسها لغير الناطقين بغير العربية من خلال كتاب سلسلة تعليم اللغة العربية أصدرته جامعة الإمام محمد بن سعود الإسلامية بالمملكة العربية السعودية، بحيث أن هذا الكتاب يدرس في شتى الجامعات ومعاهد تعليم اللغة العربية في إندونيسيا.الكلمات الرئيسية : مهارة الاستماع، تدريس اللغة العربية، كتاب سلسلة.